Association between dietary fibre intake and asthma (symptoms and control): results from the French national e-cohort NutriNet-Santé. Issue 9 (14th November 2019) - Andrianasolo, Roland M.; Hercberg, Serge; Kesse-Guyot, Emmanuelle; Druesne-Pecollo, Nathalie; Touvier, Mathilde; Galan, Pilar; Varraso, Raphaëlle
Abstract: Despite growing evidence suggesting a potential health benefit of high fibre intake for the prevention of chronic inflammatory diseases, studies regarding the role of total dietary fibre intake, types and sources of fibre on asthma are lacking. The present study aimed to investigate the cross-sectional association of dietary fibre intakes and source of fibre with the asthma symptom score and asthma control. A total of 35 380 participants from the NutriNet-Santé cohort were included. Asthma was defined by the asthma symptom score and asthma control by the asthma control test. Fibre intake (g/d) was categorised according to sex-specific quintiles. Multi-adjusted negative binomial regressions were used to evaluate the association between dietary fibre with the asthma symptom score and logistic regressions with asthma control. Participants were aged on average 54 years. After adjustment for confounders, higher intake of total, soluble, insoluble fibres from cereals, fruit and seeds were significantly negatively associated with the asthma symptom score both among women and men; OR for the highest quintile of total dietary fibre compared with the lowest quintile were 0·73 (95 % CI 0·67, 0·79) in women and 0·63 (95 % CI 0·55, 0·73) in men. We also found inverse significant associations between total, soluble and insoluble fibre with uncontrolled asthma; OR for participants in the highest quintile of total dietary fibre was 0·72 (95 % CI 0·55, 0·95) in women and 0·45 (95 % CI 0·26, 0·79) in men. Our results suggested that higher intake of dietary fibre, mostly insoluble fibre and fibre from cereals, was associated with fewer asthma symptoms and greater asthma control.